Asymmetric Long-Range Surface Plasmon Polariton Waveguides for Sensing Applications - Qiqin Wei; Jing Xiao; Shirong Chen; Quan Wang; Miao Cai; Daoguo Yang; Hongbo Qin (IEEE Photonics Journal)
A plasmonic sensing device based on an asymmetric long-range surface plasmon polaritons waveguide is proposed and investigated. The sensing structure consists of a microchamber and a gold strip with a cover layer, which is located on a dielectric supported by a silicon substrate. The optical and sensing properties of the device were studied using a finite element method. The sensitivity of the designed structure approaches 7.74 W/RIU for optimal sensing length and the limit of detection is 5.17 × 10−7 RIU. The proposed device is appropriate for a wide range of sensing applications, in fields that include biochemistry, environmental science, food safety, and medicine.